Integratively Genomic Analysis Reveals the Prognostic and Immunological Characteristics of Pyroptosis and Ferroptosis in Pancreatic Cancer for Precision Immunotherapy - Yu, Ting; Tan, Huaicheng; Liu, Chunhua; Nie, Wen; Wang, Yang; Zhou, Kexun; Shi, Huashan (Frontiers in Cell and Developmental Biology, 2022)
The non-apoptotic cell death processes including pyroptosis and ferroptosis have implicated in the progression and therapeutic responses of pancreatic adenocarcinoma (PAAD). However, the extent to which the pyroptosis and ferroptosis influences the tumor biology remains ambiguous, especially in the PAAD that characterized with “cold” immunity. Considering the heterogeneity among different patients, it was more practical to quantify the distinct cell death profiles in individual tumor sample. Herein, we developed a pyroptosis-ferroptosis (P-F) score for PAAD patients in The Cancer Genome Atlas (TCGA) database. The high P-F score was associated with active immune phenotype, decreased genomic alterations, and significantly longer survival. The good accuracy of P-F score in predicting overall survival (OS) was further confirmed in the TCGA-PAAD, ICGC-PACA-CA and E-MTAB-6134 cohorts. Besides, one immunotherapy cohort (IMvigor210 dataset) has verified the patients with high P-F scores exhibited significant advantages in therapeutic responses and clinical benefits. The sensitivity to chemotherapeutics was analyzed through the Genomics of Drug Sensitivity in Cancer (GDSC), and patients with low P-F score might be more sensitive to the paclitaxel and 5-fluorouracil. Collectively, the P-F score based on the systematic evaluation of the cell death profiles could serve as an effective biomarker in predicting the outcomes and responses of PAAD patients to the treatments with chemotherapeutic agents or immunotherapies.